Psychoanalysis A New Overview - Irtelli, Floriana; Marchesi, Barbara; Durbano, Federico (IntechOpen, 2021)
This book provides a comprehensive overview of the contemporary evolution of psychoanalytic thought and significant development in psychoanalytic methods, relating this information with other scientific disciplines and approaches. It also discusses the modern approach to psychoanalysis, psychoanalytic contributions to modern experience and culture, new empirical research derived from the practice of psychoanalysis, and more.